Imaging the neural correlates of tinnitus: a comparison between animal models and human studies - Middleton, Jason W.; Tzounopoulos, Thanos (Frontiers in Systems Neuroscience, 2012)
Tinnitus is the perception of a sound, a so-called “phantom sound,” in the absence of a physical sound. The phantom perception persists after transection of the auditory nerve, indicating that the site of tinnitus manifestation is in the central nervous system. Imaging studies in tinnitus sufferers have revealed increased neuronal activity—hyperactivity—in subcortical and cortical auditory centers. These studies have demonstrated that non-auditory brain areas, such as the limbic system, are involved in the neural basis of tinnitus, Finally human imaging studies have led to novel hypotheses for the generation of tinnitus, such as the thalamocortical dysrhythmia hypothesis. Imaging in animal models of tinnitus exhibit similarities to results from human studies and have revealed hyperexcitability of auditory brain centers as a neural correlate of tinnitus. We propose that the comparison between animal model and human studies will aid in the design of appropriate experimental paradigms aimed at elucidating the cellular and circuit mechanisms underlying tinnitus.